Legal Aspects of Data Security Cooperation in the Development of Digital Economy of the Shanghai Cooperation Organization Member States - Sairambaeva, Zh.T.; Ju, Zhang (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
Digital economy cooperation has become an emerging area of cooperation for the SCO. However, data security issues such as data leakage and cross-border data flow risk have been highlighted. The fundamental reason is that there are obvious differences in data security laws and the lack of legal mechanism for data security cooperation. Therefore, according to the characteristics of the SCO member states, the basic principles and the idea of legal mechanism. These legal mechanism ideas including win-win cooperation data security concept, a data security cooperation platform, digital products and digital services supply chain security legal framework system, protect the citizens of personal data security legal mechanism, form a "good data protection" and "data development and utilization" system environment. At the same time these mechanisms must provide data subjects between "data resources and data assets" "sharing, reciprocity, trading, exchange" activities of data security cooperation system compatibility. The legal mechanisms of data security cooperation in the SCO digital economy cooperation should be a sustainable development and dynamic legal mechanism.